Analysis of Print Purchase on Demand Titles Ordered via Interlibrary Loan: A Collection Development Perspective. Issue 2 (2nd April 2016) - Kochan, Carol; Duncan, Jennifer
ABSTRACT: This article examines data from five years of titles ordered as part of an academic research library's purchase on demand program (POD-ILL) for print titles originally requested through interlibrary loan. The study evaluates a variety of factors: patron departments, campus location, and status; the subject areas of the books acquired; cost; and publishers. Assessment of POD-ILL data may assist a collection management librarian to determine the value of having patrons contribute to collection development decisions. In addition, subject librarians can use the data to evaluate approval and demand-driven acquisition profiles.